The Relationship of Mathematical Communication Ability to Learning Outcomes of Grade IV Students in Elementary School: Hubungan Kemampuan Komunikasi Matematis Terhadap Hasil Belajar Siswa Kelas IV di Sekolah Dasar - Peni Suci Hidayati; Tri Linggo Wati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe the relationship and the relationship between mathematical communication skills and fourth grade learning outcomes at SDN Kwedenkembar. This type of research is correlation research. The research subjects were fourth grade students at SDN Kwedenkembar. Data collection techniques used include a mathematical communication ability questionnaire, daily test scores, PTS scores and PAS scores. The prerequisite test in this study used the data normality test, linearity test and hypothesis testing. The results of this study indicate that there is a significant relationship between mathematical communication skills and fourth grade students' learning outcomes at SDN Kwedenkembar. The results of hypothesis testing obtained a significance value of 0.000 <0.05 so that ha is accepted and h0 is rejected. The magnitude of the correlation coefficient shows the value of rcount > rtable (0.638 > 0.381), based on the value of the correlation coefficient, the correlation in this study is strong and positively related, which means that if the value of mathematical communication skills increases, the value of learning outcomes will also increase.